2017
DOI: 10.3390/polym9120725
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Polymeric Structures with Special Wettability and Their Applications: An Overview

Abstract: Abstract:It is not unusual for humans to be inspired by natural phenomena to develop new advanced materials; such materials are called bio-inspired materials. Interest in bio-inspired polymeric superhydrophilic, superhydrophobic, and superoleophobic materials has substantially increased over the last few decades, as has improvement in the related technologies. This review reports the latest developments in bio-inspired polymeric structures with desired wettability that have occurred by mimicking the structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 234 publications
(540 reference statements)
0
32
0
Order By: Relevance
“…In the Cassie-Baxter state, air trapped in the grooves between surface features forms a composite (air/solid) hydrophobic surface, leading to a larger contact angle compared to the contact angle θ with a flat surface. In contrast, in the Wenzel state, the liquid on the surface enters the grooves, leading to higher surface wettability, due to the increase in contact area [7,39,40]. Therefore, it can be concluded from the Wenzel equation that surface roughness amplifies the wettability of the original surface.…”
Section: Wetting State Of a Real Solid Surfacementioning
confidence: 99%
“…In the Cassie-Baxter state, air trapped in the grooves between surface features forms a composite (air/solid) hydrophobic surface, leading to a larger contact angle compared to the contact angle θ with a flat surface. In contrast, in the Wenzel state, the liquid on the surface enters the grooves, leading to higher surface wettability, due to the increase in contact area [7,39,40]. Therefore, it can be concluded from the Wenzel equation that surface roughness amplifies the wettability of the original surface.…”
Section: Wetting State Of a Real Solid Surfacementioning
confidence: 99%
“…The super-hydrophobic coating is a kind of coating with special surface wetting properties, its contact angle with water is greater than 150° and the rolling angle is less than 10° [ 6 , 7 , 8 ]. In 1997, W. Barthlott et al studied the self-cleaning ability of plants and discovered for the first time that there are micro-nano-scale rough structures on the surface of the lotus leaf, and proposed the lotus leaf effect [ 9 , 10 ]. The super-hydrophobic surface has the excellent self-cleaning ability and can quickly remove surface water [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1997, the German botanist Baethlott [31] reported that water droplets sit on lotus leaves with water contact angle larger than 150° and roll off easily carrying away the dust when tilting and this phenomenon is defined as the “lotus effect”. This extraordinary property is named as superhydrophobicity and self-cleaning [32,33,34]. Further investigation showed that lotus leaf is comprised of nano/microhierarchical structures and they are coated with low surface energy wax to reduce surface energy, thereby delivery superhydrophobicity and self-cleaning property (Figure 2a) [29,30].…”
Section: Introductionmentioning
confidence: 99%